Changes in visual abnormalities after endonasal endoscopic surgery for giant pituitary adenoma with extension to the ventricular system (Ukrainian Journal of Ophthalmology, 2024)
Purpose: To assess the features of visual impairments in patients with giant pituitary adenoma (GPA) with extension to the ventricular system showing different directions of tumor growth and chiasm positions to improve the early diagnosis of the chiasmal syndrome.Material and Methods: We retrospectively examined medical records of 41 patients with GPA showing extension to the ventricular system who were treated at the Endonasal Neurosurgery Department, the Romodanov Neurosurgery Institute between 2016 and 2021. Patients were divided into three groups based on the direction of tumor extension and chiasm position: group 1, antesellar extension and/or postfixed chiasm (14 patients); group 2, suprasellar extension and/or normal chiasm (12 patients); group 3, retrosellar extension and/or prefixed chiasm (15 patients). Patients underwent clinical neurological, otoneurological and eye examination.Results: Of the 41 patients, 38 (92.7%) had reduced visual acuity and/or or visual field defects. In the current study, 53.7% of patients had nonfunctional GPA, which makes diagnosis in the early stages (when the tumor is small) challenging. Bitemporal hemianopsia and severe chiasmal syndrome were prevalent among patients with normal or postfixed chiasm, and 14% of eyes were blind among these patients. Moderate chiasmal syndrome was prevalent, 1.2% of eyes were blind and 7.3% of patients had no visual deficiency among patients with prefixed chiasm. In addition, homonymous hemianopsia was found in 7 patients (17.5%) with prefixed chiasm, and was caused by the effect on the posterior chiasm and visual pathways. Mean visual acuity and visual field mean defect (MD) values were statistically significantly better in patients with post-fixed or normal chiasm.Conclusion: Visual field defects atypical for tumors of the chiasmal and sellar region may emerge depending on the topographic relationship between the chiasm and the GPA.
Keywords: Giant pituitary adenoma; age-related macular degeneration; position of the chiasm; compressive optic neuropathy; homonymous hemianopsia; endoscopic transnasal surgery